Messenger RNA (mRNA) based therapeutics in transforming cardiovascular care: Progress, regulatory challenges and future perspectives - Mudassir Khan; Umberto M. Musazzi; Sara Manellari; Nayla Mouawad; Giulia Damiano; Raffaella Rinaldi; Angela Raucci; Sarah Costantino; Francesco Paneni; Paola Minghetti; Giulio Pompilio; Maria Cristina Vinci (Pharmacological Research)
Messenger RNA (mRNA) is emerging as a new tool for therapeutic intervention, providing a transient, programmable platform for the treatment of complex diseases. Unlike DNA-based therapies, mRNA does not integrate into the genome and is considered more safe. The success of mRNA vaccines, combined with advances in mRNA technology and unmet needs in cardiovascular disease (CVD), has led to increased interest in expanding the use of this technology beyond infectious diseases. However, there are several challenges to overcome, including mRNA stability, delivery efficiency, immunogenicity, and regulatory standardization. This review examines advances in mRNA design, delivery platforms, and therapeutic applications in CVDs, emphasizing the need for a clear regulatory framework to facilitate clinical translation. The establishment of consistent regulatory guidelines will be a critical step in ensuring the safety and efficacy of mRNA-based cardiovascular therapies, potentially facilitating their widespread adoption. The future direction of research in mRNA formulation, personalized medicine approaches, and the refinement of regulatory policies will determine the landscape of next-generation cardiovascular therapeutics.